How Family Members Experienced a Family-Focused Atrial Fibrillation Intervention in an Outpatient Setting-A Qualitative Study - Stine Rosenstrøm MSc, RN; Wan Xui Chou MScN, RN; Anne Brødsgaard PhD, MPH, RN (SAGE Publishing, 2022)
Introduction Family-focused nursing has gained ground worldwide, and a range of healthcare systems are now practicing family-focused nursing, which has been shown to increase the quality of care. Even so, a lack of research remains into family-focused nursing for various groups of patients in clinical practice. Objectives The purpose of this study was to explore how family members (FMs) of patients with atrial fibrillation (AF) experienced a family-focused nursing intervention in a clinical outpatient setting. Methods This was a qualitative phenomenological interview study employing Reflective Lifeworld Research (RLR) to explore humans' lived experiences. The data reported herein were derived from semi-structured interviews with seven FMs of patients with AF who participated in a clinical trial which tested a family-focused intervention in a Cardiology outpatient clinic treating patients with AF. The transcribed interviews were analyzed in four phases which is an iterative process as proposed by Dahlberg and Dahlberg. Findings The essence of the phenomenon was experiencing less panic and finding peace, which emerged from the following four patterns. (1) The FMs' post-AF experience, (2) Enhanced understanding and knowledge of AF, (3) Personal interaction with a nurse specialist and (4) AF becomes manageable. A space facilitating reflection upon the disease and daily life with the disease was established through group sessions and family conversations. Conclusion A family-focused nursing intervention facilitated by specialized nurses with extensive communication skills filled a knowledge gap related to AF thereby reducing panic and increasing peace among FMs. Furthermore, the intervention facilitated family awareness of their resources to bring about change, regain balance, and enhance well-being in their everyday lives and initiated a healing process in the families. Future interventions for patients with AF should consider FMs as well as patients as an entity of care.